PREVALENCE, KNOWLEDGE AND ATTITUDE OF BUTCHERS TOWARDS FASCIOLIASIS PARASITE AT SELECTED ABATTOIRS IN ABEOKUTA METROPOLIS, OGUN STATE, NIGERIA - Adeleke, G.A.; Olaleye, O.O.; Folorunsho, A.O.; Ologbon, O.A.C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the prevalence, knowledge and attitude of butchers towards Fascioliasis parasite at selected abattoir in Abeokuta, Ogun State. A purposive sampling procedure was employed, collecting data with structured questionnaire and key informant interview; which were descriptively analyzed. From the study, 86.09% of the respondents were male; aged 25 to 30 years, practiced Islamic religion; married (72.17%); had primary education; and had between 5 and 10 household members. Only 11% of them had post-primary school education, but with 11 to 20 years’ experience as abattoir operators. 45% of the butchers viewed fascioliasis as belonging to the class of zoonotic helminthes. Most butchers admitted the parasite primarily infects the liver, causing enlargement (40%), color changes (28%), and liver lesions (10%). All the butchers had pre-knowledge of Fascioliasis as a common parasite, stating its attendant effects as including weight loss (60%) and loss of appetite (20%). The study revealed butchers’ pre-knowledge of Fascioliasis prevalence in the study area, propelling them to undergo various handling and safety trainings regarding meat dressing/processing. 70.43% of the butchers had not recorded any incidence of Fascioliasis infection, despite their relatively long abattoir operation experiences. All the respondents believed that Fascioliasis causes revenue loss. Common mitigating practices against Fascioliasis’ spread in the study area include effective cattle deworming; routine meat inspection, and enforcement of relevant government policies by the inspectorate health professionals. The study concludes that Fascioliasis is a well-known parasite among butchers/operators of abattoirs in Abeokuta metropolis, causing economic loss through reduction in sellable animal parts, thus, leading to reduced income. Routine inspection on meat stocks by health workers is impactful, mitigating economic losses to butchers. The study recommended sustainable control programs for Fascioliasis, including public awareness about the economic importance of the parasite; and educating butchers and meat vendors on government sustainable abattoir operation policies.